The Role of Digital Literacy on the Performance of Christian Religious Higher Education Lecturers in the Era of Society 5.0 - Candra Nugraha Wati; Fakhruddin Fakhruddin; Dwi Yuwono Puji Sugiharto; Masrukan Masrukan (International Conference on Science, Education, and Technology, 2023)
Christian Religious Higher Education (CRHE) has a contribution in realizing Indonesia's national education goals, namely educating the life of the nation. One of the challenges in the world of education in the era of society 5.0 is the rapid development of technology that integrates with life. This requires every CRHE lecturer to be able to adapt to change and have digital literacy skills so that they can support lecturer performance. This study aims to analyze the role of digital literacy on the performance of CRHE lecturers in the era of society 5.0 and the challenges of lecturer digital literacy. This research method is qualitative, with data collection techniques in the form of interviews and documents from relevant research journals. The results of the study show that digital literacy plays an important role in the performance of CRHE lecturers, namely: 1) the dimensions of technical skills, digital literacy can make it easier for lecturers to use digital technology, 2) the cognitive dimension, digital literacy enables lecturers to manage, analyze and synthesize digital resources, and 3) the social dimension, digital literacy enables lecturers to build networks with other researchers and communicate effectively with colleagues, students and the community.